2011
DOI: 10.1017/s1471068411000378
|View full text |Cite
|
Sign up to set email alerts
|

Contextual hypotheses and semantics of logic programs

Abstract: Logic programming has developed as a rich field, built over a logical substratum whose main constituent is a nonclassical form of negation, sometimes coexisting with classical negation. The field has seen the advent of a number of alternative semantics, with KripkeKleene semantics, the well-founded semantics, the stable model semantics, and the answer-set semantics standing out as the most successful. We show that all aforementioned semantics are particular cases of a generic semantics, in a framework where cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Given a set of rules P, we use [ P ] to denote the set of literals captured by the Kripke-Kleene semantics of P, that is, the set of all literals all of whose closed instances can be generated from P. In [23], we showed that semantics of P different to the Kripke-Kleene semantics can be captured by [ P + Ω E ] where E is a set of literals and P + Ω E is a set of rules obtained from P by selecting some occurrences of literals in the bodies of P's rules-Ω determines which occurrences of literals to select-and assuming that the members of E hold in the contexts selected by Ω in P. For instance, the well-founded semantics [11] can be obtained by:…”
Section: Can_fly(x) ← Bird(x) Not¬can_fly(x)mentioning
confidence: 99%
See 4 more Smart Citations
“…Given a set of rules P, we use [ P ] to denote the set of literals captured by the Kripke-Kleene semantics of P, that is, the set of all literals all of whose closed instances can be generated from P. In [23], we showed that semantics of P different to the Kripke-Kleene semantics can be captured by [ P + Ω E ] where E is a set of literals and P + Ω E is a set of rules obtained from P by selecting some occurrences of literals in the bodies of P's rules-Ω determines which occurrences of literals to select-and assuming that the members of E hold in the contexts selected by Ω in P. For instance, the well-founded semantics [11] can be obtained by:…”
Section: Can_fly(x) ← Bird(x) Not¬can_fly(x)mentioning
confidence: 99%
“…Our aim in this paper is to present a denotational semantics to logic programming as a complement to the operational semantics presented in [23], so that:…”
Section: Can_fly(x) ← Bird(x) Not¬can_fly(x)mentioning
confidence: 99%
See 3 more Smart Citations